Keberlanjutan Dana Pensiun Syariah dalam Kompetisi Industri Keuangan Nasional - Anwar Maulana; Aulia Ankin Nadella (MUARA EKONOMI : Jurnal Ilmiah Ilmu Ekonomi, Manajemen & Bisnis, 2026)
This study aims to analyze development strategies that can be implemented by Islamic pension funds in order to compete amidst the dominance of conventional pension funds in Indonesia. Using qualitative literature study methods and a SWOT analysis approach, this study identifies the strengths, weaknesses, opportunities, and threats faced by Islamic pension funds. The results of the study indicate that although Islamic pension funds still have a relatively small number of participants and assets compared to conventional pension funds, there is a great opportunity to grow, especially since the majority of Indonesia's population is Muslim and public awareness of Islamic financial principles is increasing. This study produced 12 development strategies consisting of a combination of strengthopportunity (S-O), weakness-opportunity (W-O), strength-threat (ST), and weakness-threat (W-T) strategies that can be used as guidelines in optimizing the growth of Islamic pension funds in Indonesia